2018
DOI: 10.1186/s40463-018-0314-7
|View full text |Cite
|
Sign up to set email alerts
|

Modified bolster dressing with continuous suction improves skin graft survival for an oral cavity wound

Abstract: BackgroundSkin engraftment of intraoral defects is known to be inconsistent due to mobility of the oral structure, uneven wounds, and accumulation of saliva under the skin graft. To improve the success rate of oral skin graft, we proposed a novel and simple dressing technique for intraoral skin graft to control saliva accumulation, in comparison with the conventional bolster dressing.MethodsWe retrospectively reviewed 31 patients reconstructed with skin graft in their intraoral defect. The patients were divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Other studies have reported total graft failure rates of 9.5-10% for intraoral STSGs [9]. Furthermore, the partial necrosis rate has been reported to be 12.3-57.1% [9,10]. In this series, the button sandwich technique combined with a tie-over technique demonstrated an excellent engraftment rate (90.5%) and no cases of total graft failure were encountered.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Other studies have reported total graft failure rates of 9.5-10% for intraoral STSGs [9]. Furthermore, the partial necrosis rate has been reported to be 12.3-57.1% [9,10]. In this series, the button sandwich technique combined with a tie-over technique demonstrated an excellent engraftment rate (90.5%) and no cases of total graft failure were encountered.…”
Section: Discussionmentioning
confidence: 53%
“…The success rate of STSG in the oral cavity has been reported to be 33-75% [8]. Other studies have reported total graft failure rates of 9.5-10% for intraoral STSGs [9]. Furthermore, the partial necrosis rate has been reported to be 12.3-57.1% [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Gentle pressure from a layered dressing is applied, or small sutures are used to hold the graft in place. A non-adherent sterile dressing is then applied to the raw donor area for about three to five days to protect it from infection (Lee et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…7 Skin grafting is a simple procedure and can be an option for reconstructing these defects; however it has certain drawbacks like contraction, abnormal pigmentations and high risk of graft failure especially when used in intraoral reconstruction because of possibility of saliva collection underneath. 8,9 The pedicled temporalis muscle flap has its role for craniofacial and intraoral reconstruction especially retromolar area and cheek resection defects., The commonest problem with this flap is postoperative trismus which can be prevented by performing coronoidectomy that increase the operative time and adds morbidity at the operative site. 10 We do believe that trismus is caused by fibrosis, especially after radiotherapy, in comparison with nasolabial flaps no trismus were encountered in any of our patients including those who received postoperative radiotherapy and this stands on for the rich blood supply of the nasolabial flap.…”
Section: Discussionmentioning
confidence: 99%